Desenvolvimento de biossensores capacitivos constituídos de monocamadas peptídicas nanometricamente estruturadas - Piccoli, Júlia Pinto [UNESP] (2015)
Early diagnosis plays an important role in the successful treatment of diseases. The development of label free devices, coupled with the electroanalytical techniques allows the development of low cost and fast methods for evaluating the stage of disease and/or treatment efficacy. Redox capacitive biosensors have recently been introduced as a platform of electroanalytical assays with great potential for the development of this type of device. In this study peptides labeled with a redox probe, in the case ferrocene (fc), were synthesized capable to form self-assembled monolayers on metal interfaces for use in diagnostic assays. The sequences of peptides: Ac-Cys-Ala-Ala-Lys(fc)-Ala-Ala-Fc-COOH and Lys-Ala-Cys-NH2 were synthesized on solid phase: 1) the side chain of the cysteine residue is covalently bound to the gold electrode (sulfur group); 2) the C-terminal or side chain of Lys accounted individually by coupling the anti-CRP; 3) the side chain of Lys or the N-terminal were used individually to fix the ferrocene group in the peptide chain. Despite the syntheses have shown difficulty, the peptides were successfully obtained. After peptide attachment to gold containing ferrocene, the antibody which identifies C-reactive protein, was attached to the system. C-reactive protein is important because it is a biomarker of inflammation and cardiovascular disease. Electrochemical techniques such as cyclic voltammetry, electrochemical impedance and capacitance spectroscopy were used to characterize the system and determinate the protein binding to the antibody. The system was developed using the capacitance to detect C-reactive protein, detection limits of 0.8 nmol L-1 and 0.31 nmol L-1 were found for the peptides Ac-Cys-Ala-Ala-Lys(fc)-Ala-Ala-Fc-COOH and Fc-Lys-Ala-Ala-Cys-NH2, respectively, and stable redox capacitive signal. Thus, the number of amino acids that forms the monolayer has shown a correlation...